Uji Potensi Limbah Panas dari Kompor Gas Satu dan Dua Tungku yang Dibuang ke Lingkungan - Jufrizal, Jufrizal; Napitupulu, Farel H.; Abdullah, Ilmi; Ambarita, Himsar; Tarigan, Dicky Adrian Sera (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2022)
This research aims to measure the temperature around the burner of a single and two-burner SNI gas stove experimentally. The method involves installing temperature sensors at various points around the burner to measure the temperature distribution during stove operation. Testing one stove with the maximum gas stove setting shows that the temperature of the flame (Tf), inner wall (Ti), and outer wall (To) has an average value of 515.7426°C, 159.4874°C, and 123 respectively. .9852°C. With the minimum gas stove setting, the average values ​​of Tf, Ti, and To are 412.9672°C, 101.7448°C, and 64.1360°C. For testing two stoves with the maximum gas stove setting, the average values ​​of Tf, Ti, and To were 666.9459°C, 146.0443°C, and 81.8967°C respectively, while for the minimum gas stove setting, The average values ​​of Tf, Ti, and To are 596.623°C, 94.6196°C, and 60.9590°C. The results of this measurement indicate that the heat lost to the environment through radiation is still significant, as can be seen from the high temperatures measured on the inner and outer walls of the plate around the burner. These findings are important for improving the design of gas stoves to increase energy efficiency and reduce heat lost to the environment.